2016
DOI: 10.1007/s00198-016-3495-9
|View full text |Cite
|
Sign up to set email alerts
|

The predicted lifetime costs and health consequences of calcium and vitamin D supplementation for fracture prevention—the impact of cardiovascular effects

Abstract: We conclude that the magnitude of potential cardiovascular side effects is crucial for the effectiveness and cost-effectiveness of CaD supplementation in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Furthermore, vitamin D deficiency has been identified as a risk factor for myocardial infarction, heart failure, and inflammatory cardiovascular disease [12-14]. Clinical reports have confirmed that vitamin D could regulate blood pressure in healthy individuals [15] and decrease high blood pressure in patients [15, 16].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, vitamin D deficiency has been identified as a risk factor for myocardial infarction, heart failure, and inflammatory cardiovascular disease [12-14]. Clinical reports have confirmed that vitamin D could regulate blood pressure in healthy individuals [15] and decrease high blood pressure in patients [15, 16].…”
Section: Introductionmentioning
confidence: 96%
“…Five of these studies (17, 18, 21–23) assessed the public health and/economic impact of dairy products (also called vitamin D-fortified dairy products, vitamin D and calcium food fortification, vitamin D-rich dairy products) while two studies (19, 20) assessed the impact of calcium and vitamin D supplementation without mentioning the specific use of dairy products. Four studies assessed the public health impact of dairy products in terms of costs, number of fractures prevented, life years gained, DALY gained or QALY gained (17, 21–23) and all studies except the study of Lotters assessed the cost-effectiveness of dairy products (or calcium and vitamin D supplementation).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies assessed the public health impact of dairy products in terms of costs, number of fractures prevented, life years gained, DALY gained or QALY gained (17, 21–23) and all studies except the study of Lotters assessed the cost-effectiveness of dairy products (or calcium and vitamin D supplementation). Four studies estimated the cost per QALY gained of dairy products (17, 1921), one assessed the cost per fracture prevented and cost per life year gained (17), and one study used a benefit-cost ratio comparing costs and fractures prevented (23). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations